STANZA AND VERSE AS A MEANS OF EXPRESSING POETIC THOUGHT IN RAUF PARFI’S WORK - Begamova Dilafruz Kholmurzaevna (Modern American Journals, 2025)
The article highlights the poetic richness of Rauf Parfi’s works, especially the poems composed in five-line stanzas (mukhammās), which, along with tercets, occupy an important place in his literary legacy. In creating these stanzas, the poet skillfully employs refrains that enhance the expressiveness of the stanza. As a result, emotions, spiritual experiences, and reflections of the inner world are harmoniously conveyed through stanza and verse. The study emphasizes how Rauf Parfi’s poetry reflects the fusion of artistic thought and poetic expression through stanzaic structures.
Keywords: Stanza, free verse, masnavi, musallas, murabba, mukhammas.